The Association of Cervical Length, Bacterial Vaginosis, Urinary Tract Infection and Premature Rupture of Membranes to The Imminent Preterm Labour - Hariyo Wirastomo Prajarto; Besari Adi Pramono (Faculty of Medicine, Diponegoro University, 2020)
Background: Research conducted at the Central General Hospital (RSUP) Dr. Kariadi Semarang in 2013 stated that out of 1,719 deliveries, 82 (5%) were preterm labor cases. Although there are many predictors for predicting imminent preterm labour, the complete prediction and prevention have not been established. Prevention of preterm labor through screening is the key to antenatal care. Good early prediction on a premature labor will provide adequate antenatal surveillance and special interventions.Objective: to analyze the relationship between cervical length, bacterial vaginosis, urinary tract infections, and premature rupture of membranes with the incidence of preterm labor.Methods: It is an observational analytic study in the form of the design of cross sectional with subject of pregnant women who experienced imminent preterm labour at gestational age 28-34 weeks and were treated at the ward of Obstetrics Gynecology Hospital Dr. Kariadi Semarang and network hospital during the study period (n=112). Subjects were assessed for the clinical risk (BV, premature rupture of the membrane, urinary tract infection) and sonography (cervical length). Statistical analysis was performed with paired t-test for normally distributed data and Mann Whitney if otherwise. Analysis of the relationship between variables and the incidence of preterm labor was carried out by the X 2 testResults: From 112 subjects, it was found that the Prevalence Ratio (PR) for cervical length, bacterial vaginosis, urinary tract infections and premature rupture of membranes to the incidence of imminent preterm labor was 2.2;2.32;1.99 and 2.36 respectively. From the multivariate analysis, it was found that bacterial vaginosis and premature rupture of membranes were the most influencing factors for the incidence of imminent premature labor with Odd Ratios of 6.497 and 21.362, respectively.Conclusion: There is a relationship between cervical length (≤25 mm ), bacterial vaginosis, urinary tract infections and premature rupture of membranes in the incidence of preterm labor.